Queer Spiritual Spaces Sexuality and Sacred Places - Yip, Andrew Kam-Tuck (2010)
Drawn from extensive, new and rich empirical research across the UK, Canada and USA, Queer Spiritual Spaces investigates the contemporary socio-cultural practices of belief, by those who have historically been, and continue to be, excluded or derided by mainstream religions and alternative spiritualities. As the first monograph to be directly informed by 'queer' subjectivities whilst dealing with divergent spiritualities on an international scale, this book explores the recently emerging innovative spaces and integrative practices of queer spiritualities. Its breadth of coverage and keen critical engagement mean it will serve as a theoretically fertile, comprehensive entry point for any scholar wishing to explore the queer spiritual spaces of the twenty-first century.